Plano de gestão para a Prefeitura Municipal de Dilermando de Aguiar - Vizcarra, Reinaldo Maia (2004)
This work search to contribute with the improvement of the attendance to the users of the Municipal City hall of Dilermando of Aguiar, in Rio Grande do Sul. For such, it was necessary to research the Municipal district in your several aspects, as well as the forms of administration of the City hall, in way to understand as this identify the users of your services and the needs of these, related with your institutional obligations. The work also approaches aspects of the quality in the public service and he/she interprets the criterion Citizens and Society, of the National Prize of the Public Administration, in way to adapt the application of your items to the nature of the services of the studied Municipal City hall. Accomplishing your main objective, the work presents an administration plan, that has as objective presents practices that take the city hall of Dilermando of Aguiar to provide satisfaction to the customers of your services, that are the citizens and the society.